TINJAUAN KONDISI FISIK ATLET PACU JALUR PANGLIMO RAJO KELURAHAN SIMPANG TIGA KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Triana Risca Enita; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to review the level of physical condition of athlete runway track Panglimo Rajo Kelurahan Simpang Tiga Kuantan Central District Kuantan Singingi. The problem in this research is the achievement that is not achieved at the runway athletes Panglimo Rajo Village Simpang Tiga District Kuantan Tengah District Kuantan Singingi. This research is a non experimental research with one-shot model study model design model which is an approach that uses one-time data collection at one session. The sample in this research is 45 people obtained by total sampling technique from population of athlete runway Panglimo Rajo line of Simpang Tiga District Kuantan Tengah Sub-district Kuantan Singingi Regency. Instruments in this study were several tests on samples with Multistage Fitness Test, Sit and Reach, and Two Hand Medicine Ball Put tests. Data processing in this study using statistical procedures with percentage analysis description. This study shows that there are 4 athletes (8.9%) who can reach the category of "good good", 11 athletes (24.4%) with "good" category, 4 athletes (8.9%) with "enough" category, 13 athletes (33.3%) with the category "medium", 5 athletes (11.1%) with the category "less", and 6 athletes (13.3%) with the category "less once". Thus from all samples amounting to 45 people obtained the average value of physical condition tests on athletes runway track Panglimo Rajo Simpang Tiga District Kuantan Central District Kuantan Singingi of 66.01, so it can be concluded that the level of physical condition of athletes runway Panglimo Rajo Line Kelurahan Simpang Tiga Kuantan Tengah District Kuantan Singingi Regency is included in the medium category. Keywords: Review, Physical Condition, Athlete Runway